Nod Factor Effects on Root Hair-Specific Transcriptome of Medicago truncatula: Focus on Plasma Membrane Transport Systems and Reactive Oxygen Species Networks - Damiani, Isabelle; Drain, Alice; Guichard, Marjorie; Balzergue, Sandrine; Boscari, Alexandre; Boyer, Jean-Christophe; Brunaud, Véronique; Cottaz, Sylvain; Rancurel, Corinne; Da Rocha, Martine; Fizames, Cécile; Fort, Sébastien; et al. (Frontiers in Plant Science, 2016)
Root hairs are involved in water and nutrient uptake, and thereby in plant autotrophy. In legumes, they also play a crucial role in establishment of rhizobial symbiosis. To obtain a holistic view of Medicago truncatula genes expressed in root hairs and of their regulation during the first hours of the engagement in rhizobial symbiotic interaction, a high throughput RNA sequencing on isolated root hairs from roots challenged or not with lipochitooligosaccharides Nod factors (NF) for 4 h or 20 h was carried out. This provided a repertoire of genes displaying expression in root hairs, responding or not to NF and specific or not to legumes. In analyzing the transcriptome dataset, special attention was paid to pumps, transporters or channels active at the plasma membrane, to other proteins likely to play a role in nutrient ion uptake, NF electrical and calcium signaling, control of the redox status or the dynamic reprogramming of root hair transcriptome induced by NF treatment, and to the identification of papilionoid legume-specific genes expressed in root hairs. About 10 percent of the root hair expressed genes were significantly up- or down-regulated by NF treatment, suggesting their involvement in remodeling plant functions to allow establishment of the symbiotic relationship. For instance, NF-induced changes in expression of genes encoding plasma membrane transport systems or disease response proteins indicate that root hairs reduce their involvement in nutrient ion absorption and adapt their immune system in order to engage in the symbiotic interaction. It also appears that the redox status of root hair cells is tuned in response to NF perception. In addition, 1,176 genes that could be considered as “papilionoid legume-specific” were identified in the M. truncatula root hair transcriptome, from which 141 were found to possess an orthologue in every of the 6 legume genomes that we considered, suggesting their involvement in essential functions specific to legumes. This transcriptome provides a valuable resource to investigate root hair biology in legumes and the roles that these cells play in rhizobial symbiosis establishment. These results could also contribute to the long-term objective of transferring this symbiotic capacity to non-legume plants.